Modeling Ambiguity in Decisions Under Uncertainty - Kahn, Barbara E.; Sarin, Rakesh K. (Journal of Consumer Research, 1988)
We present a model for predicting consumers' choices under conditions of uncertainty and ambiguity. We use the term ambiguity to distinguish the class of risky decisions for which the odds of an uncertain event are not precisely known. We show that our model predicts different decisions for individuals who are ambiguity averse, ambiguity seeking, or ambiguity indifferent, thus relaxing the constraint imposed on preferences by subjected expected utility theory.